DAMPAK PENCEMARAN LOGAM BERAT TERHADAP KUALITAS AIR LAUT DAN SUMBERDAYA PERIKANAN (STUDI KASUS KEMATIAN MASSAL IKAN-IKAN DI TELUK JAKARTA) - Lestari, Lestari; Edward, Edward (Makara Journal of Science, 2004)
Effect of Heavy Metals Pollution to Seawater Quality and Fishery Resources (Case Study on Fish Death in Jakarta Bay). Observation on heavy metals content in sea water were carried out in Jakarta Bay waters in May 2004. Heavy metals observed were Hg, Pb, Cd, Cu, Zn and Ni. This observation is conducted with fishes total death in this waters. Observation is done in Ancol beach 1 (3 stations), Ancol beach 2 (4 stations), Cilincing (3 stations), and Dadap River estuary (4 Station). The results showed that the average concentration of Hg, Cd and Cu in Ancol beach 1 were